2010
DOI: 10.1097/wno.0b013e3181c28fc0
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Achiasma and See-Saw Nystagmus in VACTERL Syndrome

Abstract: A 29-year-old man with vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal defects, and limb defects (VACTERL) presented with headache, photophobia, and worsening nystagmus. He had near-normal visual acuity and visual fields, absent stereopsis, and see-saw nystagmus. Brain MRI revealed a thin remnant of the optic chiasm but normal-sized optic nerves. Functional MRI during monocular visual stimulation demonstrated non-crossing of the visual evoked responses in the occipital cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
5
18
0
1
Order By: Relevance
“…Still visual function is relatively unaffected, with the exception of nystagmus and the absence of stereopsis. In line with previously reported achiasmic subjects (Apkarian et al, 1994; Apkarian et al, 1995; Prakash et al, 2010; Victor et al, 2000), the subjects made effective use of their vision in daily life, including sport activities and reading. They performed normal on various clinical tasks, including largely normal visual field sensitivities and no visual field defects associated with the abnormal representation of the nasal retina.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Still visual function is relatively unaffected, with the exception of nystagmus and the absence of stereopsis. In line with previously reported achiasmic subjects (Apkarian et al, 1994; Apkarian et al, 1995; Prakash et al, 2010; Victor et al, 2000), the subjects made effective use of their vision in daily life, including sport activities and reading. They performed normal on various clinical tasks, including largely normal visual field sensitivities and no visual field defects associated with the abnormal representation of the nasal retina.…”
Section: Discussionsupporting
confidence: 83%
“…This poses a substantial challenge to the organization of visual field maps and prompts potential sensory conflicts. Despite these sizable aberrant projections, achiasmic humans have relatively normal visual function (Apkarian et al, 1994; Apkarian et al, 1995; Prakash et al, 2010; Victor et al, 2000). Therefore achiasma offers a unique opportunity to study the principles governing cortical map development in humans.…”
mentioning
confidence: 99%
“…An interesting and open question is whether the presence of a regular spatial structure, such as a map, is essential for proper visual function (Horton & Adams, 2005). Neurological case studies report that achiasmic subjects (Prakash, Dumoulin, Fischbein, Wandell & Liao, 2010, Victor, Apkarian, Hirsch, Conte, Packard, Relkin, Kim & Shapley, 2000) and albino subjects (Hoffmann et al, 2003) can have spatial vision but unconventional V1 field maps. In a dramatic example, Muckli et al (2009) recently observed the case of a young girl who developed with only one hemisphere (see also Werth (2006)).…”
Section: Cortical Visual Field Mapsmentioning
confidence: 99%
“…These pRF methods have successfully been used by a small group of labs to (1) investigate the normal organization of human visual cortex (e.g., [12,29,30]), (2) measure developmental plasticity in achiasmatic and sight recovery patients [31,32], and (3) examine cortical reorganization in aged-related macular degeneration [33]. Because pRF Modeling has proven so successful, it is likely that it will eventually replace TWR as the standard method for measuring VFMs.…”
Section: An Innovative Approach To Measure the Organization Of Human mentioning
confidence: 99%